1996
DOI: 10.1002/elps.1150170205
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electrochemical detection of nonchromophoric compounds following capillary electrophoresis

Abstract: Pulsed electrochemical detection (PED) following capillary electrophoresis (CE) has been applied to the direct detection of polar aliphatic compounds. These compounds typically have poor optical detection properties and are considered to be electroinactive under constant applied potentials. The voltammetric responses at microelectrodes of model compounds were studied under various buffers and pH conditions. The detection of unsubstituted carbohydrates requires highly alkaline conditions, whereas amine-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…LaCourse et al reported the determination of nonchromophorics, thiols, disul®des by PAD and integrated pulsed amperometric detection (IPAD) following CE. IPAD is better suited to manage the large oxide-formation backgrounds accompanied by oxide-catalyzed detection of amine-and sulfur-containing compounds [83,84]. It is the ®rst group to report IPAD coupled with CE.…”
Section: Au Electrode and Auahg Electrodementioning
confidence: 99%
“…LaCourse et al reported the determination of nonchromophorics, thiols, disul®des by PAD and integrated pulsed amperometric detection (IPAD) following CE. IPAD is better suited to manage the large oxide-formation backgrounds accompanied by oxide-catalyzed detection of amine-and sulfur-containing compounds [83,84]. It is the ®rst group to report IPAD coupled with CE.…”
Section: Au Electrode and Auahg Electrodementioning
confidence: 99%
“…Advantages of PAD over chemically modified electrodes include the fact that PAD can be operated over a wider pH range and will generally have a longer lifetime. It has been used for the determination of a host of sulfur compounds, including thiols and disulfides [74,75]. Detection limits using optimized PAD were typically 0.5 mM for cysteine, glutathione, and glutathione disulfide.…”
Section: Thiol Compound Assaymentioning
confidence: 99%
“…Some peptides and proteins were detected. LaCourse and Owens [74] used CE-PAD for the determination of amino acids in mildly alkaline conditions. Fermier and Colon [97] determined the amino acids by CE-AD at a nickel microelectrode under alkaline conditions.…”
Section: Amino Acid and Peptide Assaymentioning
confidence: 99%
“…PAD com eletrodos de cobre ou ouro tem sido largamente aplicada na análise de carboidratos [220][221][222][223][224][225][226][227] . Além disso, PAD pode ser utilizada com sucesso na análise de íons metálicos 228,229 , aminoglicosídeos 230 , aminoácidos 226 e compostos com grupos contendo enxofre 226,231 .…”
Section: Detecção Amperométrica (Ad)unclassified
“…Além disso, PAD pode ser utilizada com sucesso na análise de íons metálicos 228,229 , aminoglicosídeos 230 , aminoácidos 226 e compostos com grupos contendo enxofre 226,231 .…”
Section: Detecção Amperométrica (Ad)unclassified